Bird diversity in three Ficus species in the Kuningan Lowland Forest, West Java, Indonesia - YAYAN HENDRAYANA; EMING SUDIANA; ILHAM ADHYA; AGUS YADI ISMAIL (Society for Indonesian Biodiversity, 2022)
Abstract. Hendrayana Y, Sudiana E, Adhya I, Ismail AY. 2022. Bird diversity in three Ficus species in the Kuningan Lowland Forest, West Java, Indonesia. Biodiversitas 23: 2255-2261. Frugivorous birds are an important group in tropical forests, as they promote a wide diversity of plant species and animal communities via tree seed dispersal. The presence of these avifauna depends on food, such as fruits provided by Ficus spp. This study examined the diversity of birds in three species of fruiting Ficus trees located in a secondary, natural lowland forest in Mount Tilu, Kuningan, West Java, Indonesia. Bird numbers in Ficus benjamina L., Ficus sinuata Thunb., and Ficus kurzii King were determined using the concentration count method. The data were analyzed using the Shannon–Wiener diversity index (H?), evenness index (E), and dominance index (Simpson’s D). The results showed diversity index values of H´ = 2.255, E = 0.353, and D = 0.8342 for F. benjamina; H? = 2.305, E = 0.5014, and D = 0.8376 for F. sinuata; and H? = 2.305, E = 0.5014, and D = 0.8694 for F. kurzii. The bird species with the highest number of individuals was Pycnonotus simplex Lesson, 1839 (378 individuals, 20.8%), followed by Megalaima australis (Horsfield, 1821) (320, 17.7%), Pericrocotus flammeus (J.R.Forster, 1781) (203, 11.2%), Dicaeum trigonostigma (Scopoli, 1786) (116, 6.4%) and Pycnonotus melanicterus (Gmelin, 1789) (109, 6,01%). By (Horsfield, 1821) knowing the important role of ficus trees as a source of food for various species of birds, this information becomes important and can be used by forest managers to support biodiversity conservation, especially bird conservation.